7) \( \frac{\frac{3}{3}-6}{10+\frac{4}{x}}= \)
Solución de tutoría real
Responder
Solución
Revisado y aprobado por el equipo de tutoría de UpStudy
Bonus Knowledge
To simplify the expression \( \frac{\frac{3}{3}-6}{10+\frac{4}{x}} \), start by simplifying the numerator. The numerator simplifies as follows: \[ \frac{3}{3} = 1, \text{ so } 1 - 6 = -5 \] Next, consider the denominator: \[ 10 + \frac{4}{x} \] This gives us the formula: \[ \frac{-5}{10 + \frac{4}{x}} \] Now, you can rewrite the denominator as a single fraction: \[ 10 + \frac{4}{x} = \frac{10x + 4}{x} \] Thus, the entire expression becomes: \[ \frac{-5}{\frac{10x + 4}{x}} = -5 \cdot \frac{x}{10x + 4} = \frac{-5x}{10x + 4} \] So, the final result is: \[ \frac{-5x}{10x + 4} \]